2013
DOI: 10.1007/978-1-4471-5204-0_3
|View full text |Cite
|
Sign up to set email alerts
|

3D Interaction Techniques for Bimanual Haptics in Virtual Environments

Abstract: Bimanual haptics is a specific kind of multi-finger interaction that focuses on the use of both hands simultaneously. Several haptic devices permit this form of interaction, but they are subject to a certain number of limitations for interacting with virtual environments (VEs), notably workspace size issues and manipulation difficulties with single-point interfaces. Interaction techniques exist to overcome these limitations and allow users to perform specific two-handed tasks, such as the bimanual exploration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…A multiple SPH combination approach is also popular, such as the work discussed in [2], [16]. Typical device combinations are homogeneous, although heterogeneous configurations are also possible, such as the work discussed in [17], where a Novint Falcon and a Phantom Omni were combined. There are also other efforts in building new bimanual SPHs from scratch, such as those described in [18], [19].…”
Section: Related Workmentioning
confidence: 99%
“…A multiple SPH combination approach is also popular, such as the work discussed in [2], [16]. Typical device combinations are homogeneous, although heterogeneous configurations are also possible, such as the work discussed in [17], where a Novint Falcon and a Phantom Omni were combined. There are also other efforts in building new bimanual SPHs from scratch, such as those described in [18], [19].…”
Section: Related Workmentioning
confidence: 99%
“…Fiorentino et al (2010) found that the incorporation of bimanual haptics aided CAD designers in model creation. Talvas et al (2013) describe a wide range of bimanual haptic interaction techniques Bimanual virtual assembly has been found to outperform unimanual virtual assembly in a variety of situations, including perception of weight (Giachritsis et al, 2009;Owen et al, 2005), virtual navigation for the visually impaired (Crossan and Brewster, 2006), and cooperative tasks (Gunn, 2006;Hinckley et al, 1997). The increased performance of bimanual assembly has been explained using a framework that models the two hands as two motors connected in series.…”
Section: Introductionmentioning
confidence: 99%
“…Talvas et al (2013) point out that this limitation can be addressed by developing unique software algorithms or by using unique hardware configurations. One software algorithm that expands the usable haptic workspace is the Bubble Technique proposed by Dominjon et al (2005) and modified to accommodate bimanual interaction by Talvas et al (2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When programming virtual scenarios, the manipulation is also restricted to the workspace of the haptic device. New methods such as the bubble technique [185], [186] include rate/position switching based on a division on the haptic device workspace. However, this method focuses on the movement within the scenario of different points which is not directly applicable to telerobotics in which, for instance, a robot with a robotic hand has to physically interact with the real environment; therefore, considerations to apply rate-position control to real scenarios have to be considered.…”
Section: Introductionmentioning
confidence: 99%